Cholestatic liver injury model of bile duct ligation and the protection of Huang-Lian-Jie-Du decoction by NMR metabolomic profiling1. Issue 81 (3rd September 2015) - Wei, Dandan; Liao, Shanting; Wang, Junsong; Yang, Minghua; Kong, Lingyi
<x xml:space="preserve">Abstract</x> Bile duct ligation (BDL) induced cholestasis in rats and the treatment effects of Huang-Lian-Jie-Du decoction (HLJDD) were investigated by NMR-based metabolomics approach: biphasic feature of BDL model and bilateral adjustment of HLJDD were found.